WAYS TO IMPROVE LOGISTICS PLANNING (International scientific-electronic journal “Pioneering studies and theories”, 2025)
Efficient logistics planning is essential for optimizing supply chains, reducing costs, enhancing customer satisfaction, and responding to dynamic market demands. In the era of globalization, e-commerce expansion, geopolitical instability, and digital transformation, logistics systems must become faster, more adaptive, and technologically integrated. This article provides a comprehensive and detailed examination of key strategies for improving logistics planning, including digital innovation, predictive analytics, infrastructure development, human capital investment, regulatory harmonization, and cross-sector coordination. While the study draws examples from multiple economies, the findings are universally relevant to both developed and emerging nations. Emphasis is placed on international best practices, advanced technologies, and the strategic role of logistics in national and corporate competitiveness. The logistics is determined as joint activities of various entities for integration of all processes connected with goal achievement of their business.